A dynamic model of excitation−contraction coupling during acidosis in cardiac ventricular myocytes - Crampin, E; Smith, N (2006)
Acidosis in cardiac myocytes is a major factor in the reduced inotropy that occurs in the ischemic heart. During acidosis, diastolic calcium concentration and the amplitude of the calcium transient increase, while the strength of contraction decreases. This has been attributed to the inhibition by protons of calcium uptake and release by the sarcoplasmic reticulum, to a rise of intracellular sodium caused by activation of sodium-hydrogen exchange, decreased calcium binding affinity to Troponin-C, and direct effects on the contractile machinery. The relative contributions and concerted action of these effects are, however, difficult to establish experimentally. We have developed a mathematical model to examine altered calcium-handling mechanisms during acidosis. Each of the alterations was incorporated into a dynamical model of pH regulation and excitation-contraction coupling to predict the time courses of key ionic species during acidosis, in particular intracellular pH, sodium and the calcium transient, and contraction. This modeling study suggests that the most significant effects are elevated sodium, inhibition of sodium-calcium exchange, and the direct interaction of protons with the contractile machinery; and shows how the experimental data on these contributions can be reconciled to understand the overall effects of acidosis in the beating heart.